Compulsory Licensing and Administrative Procedures in Canada - Vancise, The Honorable William J. (The Columbia Journal of Law & the Arts, 2018)
I have been asked to participate at this Symposium as past Chair of the Copyright Board of Canada (“the Board”). For over a decade, I presided over the Board’s proceedings to set tariffs on the use of copyrighted material. Although I am not an expert in intellectual property, I was fortunate to hear and decide cases including the transmission of music on the Internet, interpretation of the blank media levy, making available right, and fair dealing disputes surrounding licensing for educational institutions. The Board decides more copyright issues than any other court or tribunal in Canada. I propose to deal with the Canadian experience administering copyright with several compulsory or statutory licensing schemes. There are at least three kinds of “compulsory” licensing regimes in Canada: (1) the private copying levy on blank recording media; (2) the process of issuing licenses for “unlocatable copyright owners”; and (3) the mandatory filing of tariffs for the public performance or communication of music.1